What does Brezovljani have to do with Butmir? (Archaeologia Adriatica, 2025)
The unearthing of several fragments of ceramic vessels, with stylistic features characteristic of the Butmir culture, at the Brezovljani site (near Križevci), which has been attributed to the proto-Lengyel horizon, prompted a rethinking of the relations between two cultural phenomena: Lengyel and Butmir. This was reinforced by the fact that at Becsehely site, in the southern part of Hungarian Transdanubia, which pertains mainly to the Lengyel cultural circle, a similar situation – the presence of Butmir pottery – was also observed.
Keywords: Brezovljani; Lengyel cultural horizon of Brezovljani– Lužianky–Sé; Butimir culture; Neolithic; pottery